Effectiveness of manualized case management on utilization of evidence-based treatments for children and adolescents after maltreatment: A randomized controlled trial. (May 2017) - Ganser, Helene Gertrud; Münzer, Annika; Witt, Andreas; Plener, Paul Lukas; Muche, Rainer; Rosner, Rita; Hagl, Maria; Goldbeck, Lutz
Abstract: The objective of this study was to compare structured case management (CM) to usual care (UC) for helping victims of child abuse and neglect (CAN) with mental disorders access evidence-based treatment (EBT). N = 121 children and adolescents aged 4–17 with a history of CAN and a current mental disorder were recruited in three German states in a multi-center parallel group trial. They were randomly assigned, stratified by study site and level of psychosocial functioning, to receive CM additionally to UC or only UC. CM was delivered by trained professionals and volunteers, most of them affiliated to local child welfare agencies or NGOs. UC comprised child welfare services typically delivered in Germany. The primary outcome was EBT utilization after 6 months. Secondary outcome was the time until commencement of EBT. Outcomes were determined by semi-structured clinical interviews with assessors blinded to group allocation. Predictors of access to EBT and barriers to utilization of treatment were analyzed. The intent to treat analysis showed that after 6 months 23 of 60 participants recruited to CM (38%) and 19 of 61 participants recruited to UC (31%) were using EBT, χ 2 (1, N = 121) = 0.689, p = .261. Female gender, out-of-home placement, and home state were significant predictors of access to EBT. Less than 40% of participants across both groups were successfully referred to EBT. Access to EBT seems to be in part due to system-level barriers, namely lack of implementation of EBT in community settings. Trial Registration: DRKS00003979 German Clinical Trials Register